Implementation of Open-Source ERP-Based Fleet Management System on SMEs Transportation Service Provider - Muhammad Faisal Ibrahim; Yogantara Setya Dharmawan; Ngatini (Ikatan Ahli Informatika Indonesia (IAII), 2022)
Enterprises Resource Planning (ERP) systems can be analogized as the backbone of the information system in a company. Many large-scale companies have adopted ERP systems to increase efficiency in the company's business processes. This research departs from the issue of Small and Medium Enterprises (SMEs) that are required to use ERP to compete in the global market but cannot implement an ERP system at a high cost. However, SMEs have financial limitations in adopting high-cost ERP systems. On the other hand, many open-source ERP systems can currently be used for free but with a limited number of modules. This study focuses on implementing an open-source ERP system using Odoo software version 15 on SMEs Transportation Services Providers. The goal is to develop an open-source ERP-based fleet management system for SMEs. The system developed successfully met the company's managerial expectations. All processes previously carried out manually have been carried out using the developed system. All cross-sectional data is stored in the company's master data and can be integrated to support the decision-making process, and company archives have been well documented. Based on the results of User Acceptance Testing (UAT), 98% of the system has met the needs of SMEs. It can be concluded that the implementation of an open-source ERP-based fleet management system is very helpful in managing the business processes of SMEs Transportation Services Providers more effectively and efficiently.